(3GdGfJUGQ deG GfaQOJ Hg GdEeGejIs - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s
(3ChdgG (B:s
(3GeG HYO aEffi eeKd QSeJg GdMVQI GdSGejI GdhRjQjI GdYjOjI s
(3BNQgG (B:s
(3dCfg Cf efY ef GdhUjI ddGbGQH eG PcQhg efY ai JaVjd HYVge Ydi HYV s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis